2011
DOI: 10.1158/0008-5472.can-10-3430
|View full text |Cite
|
Sign up to set email alerts
|

6-Thioguanine Reactivates Epigenetically Silenced Genes in Acute Lymphoblastic Leukemia Cells by Facilitating Proteasome-mediated Degradation of DNMT1

Abstract: Thiopurines including 6-thioguanine ( S G), 6-mercaptopurine, and azathioprine are effective anticancer agents with remarkable success in clinical practice, especially in effective treatment of acute lymphoblastic leukemia (ALL). S G is understood to act as a DNA hypomethylating agent in ALL cells, however, the underlying mechanism leading to global cytosine demethylation remains unclear. Here we report that S G treatment results in reactivation of epigenetically silenced genes in T leukemia cells. Bisulfite g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…The resulting 28 nucleosides were then further analyzed by liquid chromatography-electrospray 29 ionization-tandem mass spectrometry (LC-ESI-MS/MS). With the developed method, 30 we are able to detect DNA and RNA methylation (5-methyl-2'-deoxycytidine, 31 5-methylcytidine, and N 6 -methyladenosine) in a single cell. We then further 32 successfully determined DNA and RNA methylation in CTCs from lung cancer 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 INTRODUCTION 48 DNA cytosine methylation (5-methyl-2'-deoxycytidine, 5-mdC) is one of the 49 most important epigenetic marks that play critical roles in a variety of cellular 50 processes, 1 including cell differentiation, 2 genome imprinting, 3 and X-chromosome 51 inactivation.…”
mentioning
confidence: 99%
“…The resulting 28 nucleosides were then further analyzed by liquid chromatography-electrospray 29 ionization-tandem mass spectrometry (LC-ESI-MS/MS). With the developed method, 30 we are able to detect DNA and RNA methylation (5-methyl-2'-deoxycytidine, 31 5-methylcytidine, and N 6 -methyladenosine) in a single cell. We then further 32 successfully determined DNA and RNA methylation in CTCs from lung cancer 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 INTRODUCTION 48 DNA cytosine methylation (5-methyl-2'-deoxycytidine, 5-mdC) is one of the 49 most important epigenetic marks that play critical roles in a variety of cellular 50 processes, 1 including cell differentiation, 2 genome imprinting, 3 and X-chromosome 51 inactivation.…”
mentioning
confidence: 99%
“…27 Demethylation of DNMT1 by LSD1 stabilizes the enzyme from protein degrading and is essential for maintaining global DNA methylation in embryonic stem (ES) cells. 28,29 Interestingly, many types of cancer show upregulation of both DNMT1 and LSD1, but a real link between the 2 epigenetic enzymes in such pathologies has to be established. The retinoblastoma protein 1 (RB1) regulator myosin phosphatase target subunit 1 (MYPT1) is also demethylated by LSD1 at Lys442, losing in such way its stability and leading to enhancement of RB1 phosphorylation.…”
Section: The Lys-specific Demethylase Lsd1mentioning
confidence: 99%
“…11 Subsequent studies showed that proteasomal degradation of DNMT1 occurs under normal physiological conditions 12 and in response to a variety of drugs. [13][14][15][16] Recently, our laboratory has shown that a quinoline-based drug, designated SGI-1027, impedes the activity of all 3 DNA methyltransferases by competing with S-adenosyl methionine and induces selective proteasomal degradation of DNMT1, causing DNA hypomethylation and reexpression of the silenced tumor suppressor genes. 17 Degradation of DNMT1 is dependent on the conserved KEN box, BAH (bromo-adjacent homology) domains, and its nuclear localization.…”
Section: Introductionmentioning
confidence: 99%